Communication Competency: The Impact of Interpersonal Communication on Student's Learning Activities - Rini Kasrah; Sidartha Adi Gautama; Resdhi Wibawa; Rina Manggalani; Widiyanto (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
Interpersonal communication involves communicators and communicants meeting face to face and allows each communicator to capture the communicator's reaction or vice versa directly, both verbally and nonverbally. Good interpersonal communication will help increase student learning activities to the fullest. This study uses a quantitative approach with a survey method. The population in this study was 113, and the sample was 66, obtained using the proportional random sampling technique. The research was conducted at the Jinarakkhita Buddhist College of Religion in Lampung with even semester student respondents. Based on the study's results, it illustrates a significant influence between interpersonal communication variables and student learning activity variables. The criterion for testing the hypothesis is to reject H0 if t count > t table and vice versa. For the t distribution used dk = (n-2) and a = 0.05. Based on the data analysis obtained tcount = 3,081 while the t table with n = 66 and a = 0.05 brought 1,668. Then it can be seen that t count> t table (3,081> 1.668) or sig (0.003≤0.05), it is concluded that H0 is rejected and Ha is accepted, so there is an influence interpersonal communication on student learning activities.